(untitled) (Sebha University Conference Proceedings, 2024)
This study was conducted in one of the farms located south of the city of Sirte in May 2023, and 45 14-day-old Ross breed meat chicks were used in the study, which were randomly distributed in three groups and each group was divided into three replicates and each replicate had 5 birds, and the treatments were as follows: The control treatment (witness 0%) is a standard leech, the second treatment is a standard leech supplemented with rosemary powder (0.3 g/kg feed), the third treatment is a standard leech supplemented with rosemary powder (0.6 g/kg feed), the experiment continued until the birds reached the age of 45 days and blood samples were taken, and the experiment included the evaluation of the following characteristics: The results of the study indicated that there was a significant difference (P˂0.05) in the level of blood glucose in the first treatment added (0.3 rosemary powder), compared to the control treatment (witness 0%) and the second treatment (0.6 rosemary powder), and a significant difference (P>0.05) in GOT for the treatment (witness 0%) compared to the rest of the treatments. There was also a significant difference (P>0.05) in ALK in the second treatment (0.6 rosemary powder) compared with the treatment (0% witness) and the first treatment added (0.3 rosemary powder), while there were no changes in mean blood lipids, total cholesterol, and triglycerides and there was no significant effect (P>0.05) on the level of liver function of the subjects. 05) For the level of liver function for the averages of enzymes, GPT, total protein, and albumin globulin, there was a clear and significant improvement in liver enzymes by lowering liver enzymes, which confirms the role of the plant in protecting the liver due to the presence of flavonoids.